Assessment of the factors affecting implementation of e-procurement in public sector of Ghana: a case study of mmda’s in central region - Mensah Paul (KNUST, 2024)
A thesis submitted to the department of supply chain and information systems institute of distance learning, in partial fulfilment of the requirements for the award of the degree of master of science in procurement and supply chain management